How and why to read and create children's digital books : a guide for primary practitioners - Kucirkova, Natalia (UCL Press, 2018)
How and Why to Read and Create Children's Digital Books outlines effective ways of using digital books in early years and primary classrooms, and specifies the educational potential of using digital books and apps in physical spaces and virtual communities.